Role of Psychological Contracts in Enhancing Employee Creativity Through Knowledge Sharing: Do Boundary Conditions of Organization’s Socialization and Work-Related Curiosity Matter? - Jiang, Boliang; Kumar, Tribhuwan; Rehman, Nabeel; Hameed, Rizwana; Kiziloglu, Mehmet; Israr, Adan (Frontiers in Psychology, 2022)
COVID-19 has had a huge impact on workers and workplaces all across the world while putting regular work practices into disarray at the same time. Apart from the obvious effects of COVID-19, the pandemic is anticipated to have a variety of social-psychological, health-related, and economic implications for individuals at work. Despite extensive research on psychological contracts and knowledge sharing, these domains of pedagogic endeavor have received relatively little attention in the context of employee creativity subjected to the boundary conditions of the organization’s socialization and work-related curiosity. This paper investigates, empirically, the role of psychological contracts in escalating employee creativity through knowledge sharing by considering the moderating role of an organization’s socialization and work-related curiosity. The response received from 372 employees of the manufacturing sector has been investigated and analyzed through Smart PLS software. The results have revealed that knowledge sharing is mediating the relationship between psychological contract and employee creative performance, whereas the moderators significantly moderate the relationships of psychological contract and knowledge sharing as well as knowledge sharing and employee creative performance accordingly. It has also been depicted that the moderating impact shown by both moderators is significantly high.